Study of Serum Calcium and Magnesium Levels in Reproductive Women Using Oral and Injectable Contraceptives - Rezwana Karim Roshny; M A Muttalib; Gazi Sharmin Sultana; Farzana Akonzee Mishu; Md Imran Khan Chayon (Journal of Enam Medical College, 2024)
Background: The oral and injectable contraceptives fulfill the human need for birth control with great effectiveness. These can effectively prevent pregnancy and alleviate menstrual disorder when used correctly. Many biochemical profiles of women taking oral and injectable contraceptives are disturbed due to metabolic alterations induced by its hormonal content. Objective: To find out the effects of oral and injectable contraceptives on serum calcium and magnesium levels. Materials and Methods: This cross-sectional comparative study was done in BIRDEM General Hospital, Shaheed Suhrawardy Medical College Hospital and Gandaria Family Planning Clinic of Nagar Shastho Kendro from July 2018 to June 2019. Study parameters serum calcium and magnesium were estimated in each case. One hundred fifty women aged 18 to 45 were included according to the inclusion criteria. They were divided into three groups－50 oral contraceptive users as group I, 50 injectable contraceptive users as group II and 50 normal healthy controls as group III. After taking the informed written consent from the study subjects, a structured questionnaire was filled in for each subject to collect data including personal identification, age, sex, chief complaints, duration of contraceptive use, socioeconomic status, demographic history, family history, genetic history, drug history, menstrual history and history of other systemic diseases. Results: The results of the study showed mean age and SD of the study subjects in Group I, Group II and Group III were 31.08±6.67, 31.60±7.83 and 36.74±6.27 years respectively. Mean (±SD) age was significantly higher in control group (Group III) than Group I and Group II (p <0.001). This study found that mean (±SD) serum calcium of the study subjects in Group I, Group II and Group III were 9.34±0.47, 9.20±0.40 and 9.14±0.49 mg/dL (p <0.05). The mean serum calcium was significantly higher in Group I compared to Group II and III. The mean value of magnesium in Group I, II and III were 0.82±0.09, 0.85±0.11 and 0.80±0.09 mmol/L respectively. There was significant increase in serum magnesium in injectable contraceptive users than oral contraceptive users and control group. Conclusion: This study concluded that oral contraceptives increased the serum calcium and injectable contraceptives increased the serum magnesium levels in comparison with control individuals and these were significant. J Enam Med Col 2022; 12(2): 95−101